2022
DOI: 10.1111/chso.12575
|View full text |Cite
|
Sign up to set email alerts
|

'It's the way they look at you': Why discrimination towards young parents is a policy and practice issue

Abstract: Qualitative research has long critiqued a simplistic association between youth parenting and poor outcomes.Despite this, the UK youth parenting policy continues to view young parents through a narrow deficit lens, focused on assumed risk rather than structural inequalities. The paper brings together the direct accounts of young parents' experiences, with ethnographic observation of practice, to argue that discrimination is the critical issue associated with being a young parent. This is then set within a wider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…Da moren fortaeller om sommerferien, og at de sidder derhjemme, begynder andre foraeldre at fortaelle om beslaegtede oplevelser med at skulle " dosere" eller afmåle" deltagelsen i fx familiefester, forlystelsesparker, og hvordan de bruger solsikkesnoren 27 , når de faerdes i offentlige rum og tager offentlig transport. Owens viser i et britisk studie også, hvordan diskrimination og ringeagtelse over for foraeldre kommer til udtryk ved stirrende blikke, og hvordan i dette tilfaelde unge mødre oplever at vaere genstand for det (Owens, 2022). Hun argumenterer for, at det både er et policy-og praksisanliggende at arbejde med, at foraeldre ikke mødes med foragt og diskrimination, og ikke at vaere medproducerende af det.…”
Section: Foraeldrenetvaerk -At (Gen)skabe Et Tilhørsstedunclassified
“…Da moren fortaeller om sommerferien, og at de sidder derhjemme, begynder andre foraeldre at fortaelle om beslaegtede oplevelser med at skulle " dosere" eller afmåle" deltagelsen i fx familiefester, forlystelsesparker, og hvordan de bruger solsikkesnoren 27 , når de faerdes i offentlige rum og tager offentlig transport. Owens viser i et britisk studie også, hvordan diskrimination og ringeagtelse over for foraeldre kommer til udtryk ved stirrende blikke, og hvordan i dette tilfaelde unge mødre oplever at vaere genstand for det (Owens, 2022). Hun argumenterer for, at det både er et policy-og praksisanliggende at arbejde med, at foraeldre ikke mødes med foragt og diskrimination, og ikke at vaere medproducerende af det.…”
Section: Foraeldrenetvaerk -At (Gen)skabe Et Tilhørsstedunclassified
“…Teenage mothers report being subjected to demeaning looks, offensive comments, and low expectations based on pervasive stereotypes (SmithBattle 2020). Owens (2022) found that young parents received discriminatory treatment for awkward gazing and being regarded as hopeless throughout the community. Moreover, participants spoke about how 'looks' they received from people meant that they avoided accessing health services or even going out because it led them to feel that others thought they were not good mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies indicate that young parents, particularly those from racialized and marginalized backgrounds, report experiencing judgment, hostility, and stigmatization from various sources and in different forums, including receiving judgmental stares and name-calling from strangers, being passed over for employment, and discrimination in health care settings (Owens, 2022; SmithBattle, 2013; Whitley & Kirmayer, 2009). A series of interviews conducted with young parents (aged 16–25 years old) from diverse backgrounds revealed that all participants reported experiencing some degree of perceived discrimination and/or judgment directly related to their intersectional identities of being young parents (Conn et al, 2018).…”
mentioning
confidence: 99%